Awareness and Decision-Making in Cryptocurrency Investment Among Students in Guwahati: A Comprehensive Study - Roy, Rituparna, Dr; Chanda, Anupam, Dr; Basumatary, Bidangsha (UI Scholars Hub, 2026)
This study investigates the awareness and decision-making processes related to cryptocurrency investment among students in Guwahati, Assam. Cryptocurrency, a form of digital money designed for online transactions without government or bank oversight, has initiated significant shifts in the global financial sector. The decentralization of cryptocurrencies offers transparency, security, and efficiency, challenging traditional financial systems. Despite the growing global interest in cryptocurrencies, their adoption faces barriers such as limited technological expertise, regulatory uncertainty, and security concerns. These issues are particularly pronounced among students, a demographic increasingly interested in digital currencies but often lacking foundational financial knowledge. The research aims to fill the gap in understanding the factors influencing cryptocurrency awareness and investment decisions among students in Guwahati. The study utilizes both primary and secondary data, collected through structured online forms and face-to-face questionnaires from 120 students across six colleges and universities in Guwahati. It employs descriptive statistics, correlation, and regression analyses to explore the relationships between awareness, investment confidence, and risk perception. Key findings reveal varying levels of cryptocurrency awareness among students, influenced by educational background and access to information. Higher awareness is associated with greater investment confidence and lower perceived risk, highlighting the importance of educational interventions. The study also underscores the need for user-friendly interfaces and regulatory clarity to support informed investment decisions. By addressing educational gaps and leveraging technological advancements, this research aims to empower students with the knowledge and tools necessary for confident participation in the cryptocurrency market. The findings contribute to the development of tailored educational programs and investment platforms, fostering a more informed and resilient investor community amidst the dynamic landscape of digital finance.